2009
DOI: 10.1111/j.1755-0998.2009.02795.x
|View full text |Cite
|
Sign up to set email alerts
|

A PCR‐based method for diet analysis in freshwater organisms using 18S rDNA barcoding on faeces

Abstract: The development of DNA barcoding from faeces represents a promising method for animal diet analysis. However, current studies mainly rely on prior knowledge of prey diversity for a specific predator rather than on a range of its potential prey species. Considering that the feeding behaviour of teleosts may evolve with their environment, it could prove difficult to establish an exhaustive listing of their prey. In this article, we extend the DNA barcoding approach to diet analysis to allow the inclusion of a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 38 publications
0
99
0
Order By: Relevance
“…Classical dietary studies have reported that B. barbus is omnivorous, eating benthic invertebrates (Cherghou et al 2002;Piria et al 2005;Corse et al 2010) and small fish (Kottelat and Freyhof 2007), with algae also present in their diet (Cherghou et al 2002;Piria et al 2005). Our stable isotope data revealed a different story with little evidence that benthic macro-invertebrates (excluding P. leniusculus) were as important to diet when compared to fishmeal pellets and P. leniusculus.…”
Section: Discussionmentioning
confidence: 99%
“…Classical dietary studies have reported that B. barbus is omnivorous, eating benthic invertebrates (Cherghou et al 2002;Piria et al 2005;Corse et al 2010) and small fish (Kottelat and Freyhof 2007), with algae also present in their diet (Cherghou et al 2002;Piria et al 2005). Our stable isotope data revealed a different story with little evidence that benthic macro-invertebrates (excluding P. leniusculus) were as important to diet when compared to fishmeal pellets and P. leniusculus.…”
Section: Discussionmentioning
confidence: 99%
“…Diet studies of these types have been applied extensively to marine taxa ranging from higher trophic levels (e.g., Deagle et al 2005;Dunn et al 2010;Méheust et al 2015) through marine birds (e.g., Deagle et al 2007;Bowser et al 2013) and fish (e.g., Moran et al 2016) to different invertebrates and lower trophic levels (e.g., Jarman et al 2002;Nejstgaard et al 2003;Blankenship and Yayanos 2005;Leal et al 2014b;Olsen et al 2014;Hu et al 2015;reviewed in Calado and Leal 2015). DNA-based approaches have also yielded breakthrough dietary analyses in complex freshwater systems (e.g., Corse et al 2010;Carreon-Martinez et al 2011;Bartley et al 2015). Most of the studies to date attest to the effectiveness of DNA-based analysis, especially when combined with morphological analysis (e.g., Casper et al 2007;Braley et al 2010;Alonso et al 2014), and they offer new insights in trophic ecology.…”
Section: Clarifying the Links Of Aquatic Food Websmentioning
confidence: 99%
“…In most animal groups, the cytochrome oxidase subunit 1 (COI) is the reference for the DNA barcoding system (Hebert et al, 2003). COI sequences libraries are available through on-line systems (such as GenBank, Bold), enabling its use in the identifications of host or prey species (Valentini et al, 2009;Corse et al, 2010;Leray et al, 2013a;Jo et al, 2014). DNA barcode techniques have been used to determine host-parasitoids webs in arthropods (Hrček and Godfray, 2014), as in Lepidoptera (Janzen et al, 2009) and Hemiptera (Gordon and Weirauch, 2015).…”
Section: Introductionmentioning
confidence: 99%